2020
DOI: 10.1096/fj.202000970rr
|View full text |Cite
|
Sign up to set email alerts
|

miR‐124‐3p increases in high glucose induced osteocyte‐derived exosomes and regulates galectin‐3 expression: A possible mechanism in bone remodeling alteration in diabetic periodontitis

Abstract: This is an open access article under the terms of the Creative Commons Attribution-NonCommercial-NoDerivs License, which permits use and distribution in any medium, provided the original work is properly cited, the use is non-commercial and no modifications or adaptations are made.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 56 publications
2
30
0
Order By: Relevance
“…45 In an animal model, it was examined a possible effect of galectin-3, as a factor in DM and bone metabolism, on periodontitis with or without DM and shown that osteocyte-derived exosomes carrying miR-124-3p may regulate galectin-3 expression of osteoblasts, especially under high-glucose conditions, suggesting a possible mechanism for DM-related alveolar bone pathologies. 46 In this study, the amount of GCF galectin-3 reached the highest values in periodontitis and the lowest values in periodontal health. In addition, it decreased with initial periodontal treatment, and this is the first clinical study in the literature to show its relationship with periodontal disease.…”
Section: Table 1 Demographic Characteristics Of the Groupssupporting
confidence: 45%
See 1 more Smart Citation
“…45 In an animal model, it was examined a possible effect of galectin-3, as a factor in DM and bone metabolism, on periodontitis with or without DM and shown that osteocyte-derived exosomes carrying miR-124-3p may regulate galectin-3 expression of osteoblasts, especially under high-glucose conditions, suggesting a possible mechanism for DM-related alveolar bone pathologies. 46 In this study, the amount of GCF galectin-3 reached the highest values in periodontitis and the lowest values in periodontal health. In addition, it decreased with initial periodontal treatment, and this is the first clinical study in the literature to show its relationship with periodontal disease.…”
Section: Table 1 Demographic Characteristics Of the Groupssupporting
confidence: 45%
“…Galectin‐3 acts as chemokine, induces monocyte and macrophage migration, contributes to the development of natural and adaptive immune responses, and participates in phagocytosis of macrophages and some microorganisms through intracellular mechanisms, supporting that it may be a positive regulator of the inflammatory response 45 . In an animal model, it was examined a possible effect of galectin‐3, as a factor in DM and bone metabolism, on periodontitis with or without DM and shown that osteocyte‐derived exosomes carrying miR‐124‐3p may regulate galectin‐3 expression of osteoblasts, especially under high‐glucose conditions, suggesting a possible mechanism for DM‐related alveolar bone pathologies 46 . In this study, the amount of GCF galectin‐3 reached the highest values in periodontitis and the lowest values in periodontal health.…”
Section: Discussionmentioning
confidence: 99%
“…Gal-3 expression can be regulated by promoter hypermethylation of the LGALS3 gene and several elements in this promoter, including putative Sp1 binding sites (GC boxes), cAMP-dependent response element (CRE) motifs, sisinducible element (SIE), nuclear factor-κB (NF-κB)-like sites and consensus basic helix-loop-helix (bHLH) core sequences [20]. Previous studies have shown that Gal-3 expression could be downregulated by miR-124-3p from osteocyte-derived exosomes [21] and Krüppel-like factor 3 (KLF-3) [22] and upregulated by Runt-related transcription factor 2 (Runx2) [23].…”
Section: Gal-3: Biochemistry and Physiological Functionmentioning
confidence: 99%
“…Western blots were performed as previously described 23 . Brie y, total protein extracts were prepared in RIPA buffer, which contained inhibitors of proteases and phosphatases.…”
Section: Western Blotsmentioning
confidence: 99%
“…Immunohistochemistry was performed as previously described 23 . Brie y, right femurs were xed in 4% paraformaldehyde for 24-48 h, decalci ed in 10% EDTA for 21 d, and embedded in para n. Decalci ed right femur sections 5 μm thick were depara nized in turpentine, 3% H 2 O 2 was used to suppress endogenous peroxidase activity, and the sections were treated with 0.1% trypsin for antigen retrieval.…”
Section: Immunohistochemistrymentioning
confidence: 99%